IMMEDIATE MANAGEMENT OF OCULAR BEE STING RESULTS IN BETTER VISUAL OUTCOME ? A CASE REPORT (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2021)
Introduction: Ocular bee stings is an uncommon environmental eye injury that can result in various ocular complications. Due to the rarity of cases and conatroversial management, there are only a few literatures reported. Unfortunately, delay in management will be fatal for patients. Purpose: To highlight early management and complication of ocular bee sting case Case Presentation: A 24-year-old man presented to our hospital with chief complaint pain and blurred vision on his right eye in the last 2 days ago after being stung by bee. A part of the sting was already revoked, and the eye was rinsed off with tap water. The visual acuity on the right eye was hand movement with corneal edema, and bee sting track seen at the cornea. The anterior chamber was covered with hypopion and fibrins. An emergency bee sting extraction was quickly performed. We found the sting pierced in a diagonal way to the iris. We injected triamcinolone acetate intracamerally to make sure the exact location and how deep the sting embedded. The visual acuity improved to 6/30 a day after the surgery, but the cornea was melted and anterior uveitis still discovered, with increasing intraocular pressure. Topical and systemic corticosteroid, oral acetazolamide, topical antibiotic, and atropine were prescribed. The last condition, 2 weeks after extraction, best corrected visual acuity became 6/12 and no anterior chamber reaction discovered with corneal scarring. Conclusions: Immediate bee sting extraction with triamcinolone acetate injection intracamerally to ensure the location of the sting can be beneficial to patient?s visual outcome..